A comparative study of intramuscular sulfate versus intravenous magnesium injection among eclampsia patients in Eastern, Uttar Pradesh, India - Kauser, Uzma; Chaudhari, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive in pregnancy is the second most common cause of maternal mortality in India. Among the hypertensive disorders that complicate pregnancy, pre-eclampsia and eclampsia stand out as major causes of maternal and perinatal mortality and morbidity. The majority of deaths due to pre-eclampsia and eclampsia are avoidable through the provision of timely and effective care to the women presenting with these complications. Objectives of this study were to find out the effectiveness of intravascular and intramuscular magnesium sulfate in management of eclampsia. To compare the side effects and complications of intravascular and intramuscular magnesium sulfate in management of eclampsia. Methods: A total 100 patients presenting with eclamptic fits reporting to the center that has been included in the study. The study has been conducted in the labor room of Nehru Chikitsalaya of B. R. D. Medical College, Gorakhpur, Uttar Pradesh for 12 months duration period. Statistical analysis of observations has been done by Chi-square test with p-value <0.05 has been considered in the study. Results: Majority of eclampsia patients belonged to 20-25 years age group (63%) followed by above 30 years of age (22%). Nearly 16% patients in IM MgSO4 group and 12% patients in IV MgSO4 received recurrence of seizure after starting of treatment (p value >0.5). About 26% patients in IM MgSO4 group and 18% patients in IV MgSO4 group had mild side effects of MgSO4 but no patients in both the group had major side effects of MgSO4. Conclusions: The study concludes that intramuscular injection of MgSO4 is painful and the chances of abscess formation that's why compliance of intramuscular MgSO4 is not very good in compared to intravascular infusion of MgSO4. The chances of Mg toxicity are more MgSO4 regimen because of the dose required in IM MgSO4 regimen is more (44gm) that of IV MgSO4 (28 gm).